Managing socio-institutional enclosure: A grounded theory of caregivers' attentiveness in hospital care. (June 2016) - Klaver, Klaartje; Baart, Andries
Abstract: Purpose: Caregivers' attentiveness is vital for healthcare quality, yet existing research lacks a specific definition and neglects its different forms and aspects. Methods: This paper presents a qualitative, grounded theory of attentiveness in hospital oncology care. Results: Our data show nine types of attentiveness. We answer the question why a caregiver practices one type of attentiveness in a certain situation, and not another type. First, it appears to be of crucial importance whether attentiveness is essential for giving care in the opinion of the caregiver. Second, the focus of attention is essential. Care given by doctors and nurses is always ambivalent; on the one hand, it concerns the body, and on the other hand, it involves the person whom that body belongs to. What is the caregiver (mainly) focused on? The significance of socio-institutional enclosure emerged as a key theme within the findings. Conclusions: Socio-institutional enclosure concerns the space a caregiver may or may not experience to break free from the preponderant institutional orientation towards the physical body of the patient. At the intersection of the influence of socio-institutional enclosure and the substance of the caregivers' concepts of care, three cultures are found that comprise the different types of attentiveness. Highlights: This paper presents a qualitative, grounded theory of attentiveness in hospital oncology care. Our data show nine types of attentiveness. We answer the question why a caregiver practices one type of attentiveness in a certain situation, and not another type. The significance of socio-institutional enclosure emerged as a key theme within the findings. This concerns the space a caregiver may or may not experience to break free from the preponderant institutional orientation towards the physical body of the patient.